Oxygen saturation profile in traumatic brain injury animal model after propofol administration - Kulsum, Kulsum; Syahrul, Syahrul; Hasbalah, Kartini; Balqis, Ummu; Suryadi, Taufik (Narra J, 2023)
Traumatic brain injury (TBI) is a traumatic that often leads to death due to untreatable cerebral hypoxia, indicated by oxygen saturation of <90%. Cerebral hypoxia is rarely monitored and thereby often overlooked as a cause of mortality and monitoring oxygen saturation is an accurate method to detect the condition. Propofol, an anesthetic agent, is commonly used in the management of TBI; however, its effect on brain tissue and cerebral hypoxia in TBI cases is not well understood. The aim of this study was to evaluate the profile of oxygen saturation in TBI animal model after propofol administration. A laboratory experimental study was conducted, involving 18 male Rattus novergicus rats (aged 4–8 weeks with weight between 150–200 grams) divided into three different treatment groups (non-TBI, TBI without propofol, and TBI with propofol). Oxygen saturation was measured regularly from day 1 to day 8 using pulse oximetry. The oxygen saturation percentages were compared between the TBI rats with and without propofol administration using independent Student t-rest. The results revealed significant reductions of oxygen saturation levels of animals within propofol-treated TBI group compared to that of the untreated-TBI group (p<0.05), with the average oxygen saturation ranging from 80.8%±6.96% vs 86.8%±5.48%. This finding suggests a reducing effect of propofol administration on oxygen saturation levels in rats with TBI and this potentially causes cerebral hypoxia.